Moving adsorption belt system for continuous bioproduct recovery utilizing composite fibrous adsorbents - Guo, Yijia; Kangwa, Martin; Ali, Wael; Mayer-Gall, Thomas; Gutmann, Jochen S.; Zenneck, Claus; Winter, Martina; Jungbauer, Alois; Fernandez Lahore, Hector Marcelo (Frontiers in Bioengineering and Biotechnology, 2023)
A continuous protein recovery and purification system based on the true moving bed concept is presented. A novel adsorbent material, in the form of an elastic and robust woven fabric, served as a moving belt following the general designs observed in known belts conveyors. The composite fibrous material that forms the said woven fabric showed high protein binding capacity, reaching a static binding capacity equal to 107.3 mg/g, as determined via isotherm experiments. Moreover, testing the same cation exchange fibrous material in a packed bed format resulted in excellent dynamic binding capacity values (54.5 mg/g) even when operating at high flow rates (480 cm/h). In a subsequent step, a benchtop prototype was designed, constructed, and tested. Results indicated that the moving belt system could recover a model protein (Hen Egg White Lysozyme) with a productivity up to 0.5 mg/cm2/h. Likewise, a monoclonal antibody was directly recovered from unclarified CHO_K1 cell line culture with high purity, as judged by SDS-PAGE, high purification factor (5.8), and in a single step confirming the suitability and selectivity of the purification procedure.